Status stunted dan hubungannya dengan perkembangan anak balita di wilayah pesisir Pantai Utara Kecamatan Lemahwungkuk Kota Cirebon - Alina Hizni; Madarina Julia; Indria Laksmi Gamayanti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2010)
Background: The problem of protein energy inadequacy is a major problem among under-fives that affects the process of child growth and development. The prevalence of stunted status among under-fives in developing countries in 2008 was estimated as much as 33%. In Cirebon Municipality the prevalence was 10.27% and in north coastal area of Cirebon Municipality was 11.4%.Objective: To identify the association between stunted status and development of under-fives at north coastal area of sub district of Lemahwungkuk Cirebon Municipality.Method: This was an observational study with a cross sectional design carried out at north coastal area of sub district of Lemahwungkuk Cirebon Municipality from November 2008 to January 2009. Subject of the study consisted of 166 under-fives and the respondents were parents of those children. Samples were chosen purposively. Research instruments consisted of questionnaire, length board, microtoise, forms, and Denver II test. Data analysis used chi square and logistic regression with confidence interval (CI) 95%.Result: There was significant association between stunted status and development of fine motor adaptive, language, and gross motor capacity. There was significant association between education of mothers and personal social, fine motor adaptive, language and gross motor development. There was significant association between occupation of mothers and personal social, fine motor adaptive, language and gross motor development. There was significant association between stunted status, education of mothers, and occupation of mothers and child development. The result of multivariate analysis showed that stunted status had greater risk for delayed language development of under-fives than other indicators of child development.Conclusion: There was no association between stunted status and child development; however stunted status had greater risk for delay in language development, and risk factors dominantly affecting child development were occupation and education of mothers.